Gambaran Tingkat Konsumsi Energi Dan Status Gizi Pada Pasien Rawat Inap di UPT Kesmas Payangan Kabupaten Gianyar Tahun 2018 - Ni Kadek Sri Chandra Devi; Ni Made Yuni Gumala; Ida Ayu Eka Padmiari (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Health center is a functional organization which organizes the unity efforts including the granting of health nutrition. The purpose of this research is to know the description of the level of energy consumption and nutritional status in patients on Inpatient health center in Payangan. This type of research is a type of observational research design the research cross sectional. This is the entire research population of patients in inpatient health center in Payangan, research performed on patients aged 18-80 years. Based on the results of sample provisions i.e. 30 samples, research conducted in May of the year 2018. Research results showed the patients hospitalization health center in Payangan with an overview of the level of consumption of energy deficits (97.1%), while more energy consumption level as much as (2.8%). Based on results nutritional status as much as normal (71.4%), nutritional status (22.8%) as much as overweight while the nutritional status of obesity as much (5.7%). The results of the level of energy consumption by as much as a normal nutritional status (100%), the level of energy consumption deficit with normal nutritional status as much as (73.5%), while the deficit with the energy consumption level of nutritional status as much as (20.5%) overweight and tiers in energy consumption deficit with the nutritional status of obesity as much (5.8%).Kyword: the level of consumption; nutritional status; the patient,